Non contiguous-finished genome sequence and description of Microbacterium gorillae sp. nov. Issue 1 (December 2016) - Hadjadj, Linda; Rathored, Jaishriram; Keita, Mamadou; Michelle, Caroline; Levasseur, Anthony; Raoult, Didier; Fournier, Pierre-Edouard; Rolain, Jean-Marc; Bittar, Fadi
Abstract Strain G3T (CSUR P207 = DSM 26203) was isolated from the fecal sample of a wild gorilla (Gorilla gorilla subspgorilla ) from Cameroon. It is a Gram-positive, facultative anaerobic short rod. This strain exhibits a 16S rRNA sequence similarity of 98.2 % withMicrobacterium thalassium, the closest validly publishedMicrobacterium species and member of the familyMicrobacteriaceae . Moreover, it shows a low MALDI-TOF-MS score (1.1 to 1.3) that does not allow any identification. Thus, it is likely that this strain represents a new species. Here we describe the phenotypic features of this organism, the complete genome sequence and annotation. The 3, 692, 770 bp long genome (one chromosome but no plasmid) contains 3, 505 protein-coding and 61 RNA genes, including 4 rRNA genes. In addition, digital DNA-DNA hybridization values for the genome of the strain G3T against the closestMicrobacterium genomes range between 19.7 to 20.5, once again confirming its new status as a new species. On the basis of these polyphasic data, consisting of phenotypic and genomic analyses, we propose the creation ofMicrobacterium gorillae sp. nov. that contains the strain G3T .